Global Trends in E-Service-Learning Framework: A Systematic Literature Review - Tirza, Juliana (Ideas Publishing, 2024)
The e-Service-Learning (e-SL) model is an option in implementing quality learning even in online learning situations. The problem that still often arises regarding the implementation of e-SL is related to how to implement e-SL in learning. This study aims to find out the design framework of the e-SL model in various parts of the world, so that it is hoped that it can become an inspiration for universities that want to implement this model. The method of this research uses a systematic literature review with the help of publish or perish (PoP) in the data search process. The selection process used PRISMA in 2020. There were 18 articles that were successfully reviewed to answer the problem on how does the framework (O) e-Service-Learning (I) compared to universities (P) globally (C) during the COVID-19 pandemic (T)? Result of this research describe that the e-SL framework for the Asian region, partner cultural conditions need to be given more attention. The Americas region the framework prioritizes communication with partners and then student training. And the e-SL framework in the European region shows more importance in the reflection aspect of this e-SL process. The implication for the practitioners and researchers, they can use these insights to customize e-SL models and examine regional influences on student learning outcomes.